2020
DOI: 10.1111/jir.12794
|View full text |Cite
|
Sign up to set email alerts
|

Using behavioural skills training via telehealth to increase teachers use of communication interventions and increase student use of speech‐generating devices in a high school functional skills classroom

Abstract: BackgroundBehavioural skills training (BST) has demonstrated effectiveness in training teachers in evidence‐based interventions to increase communication for children with limited repertoires. However, research has yet to extend to youth with developmental disabilities who are learning to communicate using speech‐generating devices. The emergent use of telehealth technology in applied behaviour analysis has been associated with greater access to therapeutic services. Although the use of telehealth has been ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 39 publications
(44 reference statements)
0
29
0
Order By: Relevance
“…Speech is considered as one of the important means of human communication, and, among the other ways of communication such as writing, body language, and gesture, it is the most direct and principal method of communication [ 1 ]. Speech could also be considered an acoustic signal that expresses what is in the human mind [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Speech is considered as one of the important means of human communication, and, among the other ways of communication such as writing, body language, and gesture, it is the most direct and principal method of communication [ 1 ]. Speech could also be considered an acoustic signal that expresses what is in the human mind [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…66,67 A systematic review on parent-implemented interventions reported that most of their studies lacked information on implementation fidelity during follow-up. 67 In the current systematic review, only one study 52 reported a high fidelity maintained during a 1-month follow-up, making it difficult to conclude whether implementation fidelity is retained once the tele-AAC live coaching is finished. Given its apparent importance, future research is strongly encouraged to explore the implemented fidelity in tele-AAC interventions after the real-time feedback is removed.…”
Section: Discussionmentioning
confidence: 90%
“…Severe visual impairments are one of the main reasons for requiring these procedural modifications. [52][53][54] For a participant with severe visual impairments, 52 incorporating a verbal 'look prompt' during the second intervention phase increased the independent SGD use by 73% compared to the intervention phase without the verbal 'look prompt'. Similarly, a participant with visual impairments 53 increased their AAC responses by 28% once the screen layout was adapted by optimizing the placement of the icons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth, when used in the delivery of behavior skills training (BST) to support skill acquisition, has demonstrated promising levels of social validity and acceptability by both practitioners and caregivers (Boutain et al, 2020 ; Carnett et al, 2021 ; Dogan et al, 2017 ; Rios et al, 2020 ). Providers have widely used BST to teach youth new skills and train both caregivers (Schaefer & Andzik, 2020 ) and practitioners (Rios et al, 2020 ) on intervention procedures and strategies.…”
mentioning
confidence: 99%